翻译与意识形态的操控 ：以 Northanger Abbey 的两个中译本为例 = Ideological manipulation on translation : a study on two translated versions of Northanger Abbey - 尚晓萌 Shang, Xiaomeng (2014)
翻译研究学派代表人物勒菲弗尔（André Lefevere)提出翻译过程中，译者应以关注原作和目的语译本之间的“文化转向（cultural turn）”为视角，而不应仅限于追求译本对原作内容形式上的忠实一致性，因而提出“翻译即改写”以及“翻译对文学名声的操控”等相关理论。本文将以勒菲弗尔的理论为基础框架，通过比较研究简·奥斯丁（Jane Austin，1775—1817）所著的英国古典小说Northanger Abbey的两个中译本，探讨意识形态对文学翻译的操纵。本文分析对比的译作是1958年麻乔志的译本和1986年孙致礼的译本，两部作品分别的中文译名均为《诺桑觉寺》，它们分别完成于中华人民共和国建国初和中国步入改革开放、思想解放的时期，都是当代中国具有代表性的历史阶段。1950年代中国文坛以“社会主义现实主义”为诗学基础，一切文学作品必需跟随“政治标准第一，文艺标准第二”的思想方针，社会意识形态指导并制约着翻译活动。麻乔志在翻译中运用删节、有意误译等翻译策略对原文进行改写，以迎合主流意识形态、道德观念、出版社的要求和读者的接受。到了1978年，中国迈入建设社会主义新阶段，文学翻译与创作开始摆脱一元化意识形态的束缚，文学领域呈现多元化的繁荣景象。因而，孙致礼的翻译开始注重原文所传达出的艺术特色和社会科学知识，他的译笔忠于原文，少有改写的迹象。两位译者对译本不同的处理方式和翻译技巧的运用，体现出不同时期意识形态和文化语境对翻译的操纵。 本文将以“意识形态（ideology）”、“诗学（poetics）”、“赞助人(patronage) ”等操纵文学翻译的基本因素为出发点，通过对比分析上述 两个中译本，深入观察目的语语境中意识形态和社会文化因素如何对译作择取、译者改写以及作品出版产生重要影响。André Lefevere is the representative of the Manipulation School, he proposes that translators should not only be faithful to the original text but also have to focus on the cultural turn between the target language and the original text. With this statement, he come up with a series of theories which include “translation is rewriting” and “the manipulation of Translation on literary fame).This thesis intends to compare two Chinese versions of Northanger Abbey written by Jane Austen(1775—1817）from the social-cultural angle under the guidance of manipulation theory by Lefevere. Two translated versions of Northanger Abbey are used for comparison in this thesis. One was translated by Ma Qiaozhi in 1958,which was the beginning of a new Chinese nation and the other by Sun zhili in 1986,when “thought liberation” happened and China stepped up to the reform and opening up period. Both of them are the typical period in Chinese history. In 1950s, the poetics of Chinese literature was based on socialist realism and all literatures must follow the ideological guidelines. Translation were restrained by Social ideology .Ma Qiaozhi rewrited the original texts by using different translation strategies such as abridging, intentional mistaken translation to cater the dominant ideology, the moral idea, the publisher and the readers. In 1978 when China stepped into the period of socialism construction, translation and composing of Literature started to extricate themselves from the unitary ideology and flourished. The translation by Sun Zhili focused on the artistic features and social scientific knowledge conveyed by the original text. He was faithful to the original text and there was very few indications of rewriting found. The different strategies used by the two translators proved the manipulation of ideology and dominant poetics on translation at different historical times.This thesis will compare the two Chinese versions within the framework of manipulation factors, ideology, poetics and patronage and find out how the ideology and social culture influence the choosing, rewriting and publishing of the texts.